Influence of Health Education on Nurses' Perceptions and Attitudes in Emergency Department Triage - Sholehah, Baitus (Fakultas Kesehatan, Universitas Nurul Jadid, 2025)
Introduction: Compliance with standard operating procedures (SOPs) in intravenous (IV) infusion is essential for patient safety and quality of care. Nurses play a pivotal role in implementing SOPs, and their level of knowledge may significantly influence their adherence.. Objectives: This study aimed to examine the correlation between nurses’ knowledge levels and their compliance with intravenous infusion SOPs in the emergency department. Methods: A cross-sectional correlational study was conducted involving 116 nurses in the emergency department of RSU dr. H. Koesnadi Bondowoso. Data were collected using structured questionnaires to assess knowledge and direct observation checklists to evaluate SOP compliance. Spearman’s rho was used for statistical analysis with a significance level set at p < 0.05. Results: Of the 116 nurses, 88.8% had good knowledge, 6.0% had moderate knowledge, and 5.2% had poor knowledge. Full compliance was observed among nurses with good knowledge, while non-compliance was highest among those with poor knowledge. A strong positive correlation was found between knowledge and compliance (Spearman’s r = 0.730, p = 0.001). Conclusions: There is a significant positive association between nurses’ knowledge levels and their compliance with IV infusion SOPs. Enhancing nurses' knowledge through continuous education and monitoring is essential to promote safe and standardized nursing practices.